2008
DOI: 10.1186/1471-2172-9-33
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of total IgE among school children living in the rural Tropics: importance of geohelminth infections and effect of anthelmintic treatment

Abstract: Background: The environmental factors that determine the elevated levels of polyclonal IgE observed in populations living in the Tropics are poorly understood but may include geohelminth infections. We investigated the association between geohelminth infections and total IgE levels in school children in rural tropical Ecuador, and assessed the effect on IgE of repeated anthelmintic treatments over a period of 12 months. The study was nested within a clusterrandomized study that randomized 68 schools to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 25 publications
(38 reference statements)
4
41
0
4
Order By: Relevance
“…Such findings are consistent with observations in studies conducted in Nigeria [47, 48], Ecuador [49], Venezuela [50], Spain [26], and Brazil [41, 51, 52]. Helminth-induced IgE is mostly characterized by a nonspecific polyclonal stimulation with only a small fraction of parasite-specific IgE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such findings are consistent with observations in studies conducted in Nigeria [47, 48], Ecuador [49], Venezuela [50], Spain [26], and Brazil [41, 51, 52]. Helminth-induced IgE is mostly characterized by a nonspecific polyclonal stimulation with only a small fraction of parasite-specific IgE.…”
Section: Discussionsupporting
confidence: 91%
“…Other researchers have made the same observation [49, 51, 56]. Some studies have shown that specific IgE levels reflect the parasite infection intensity; therefore, higher specific antibody levels would be expected in lightly infected individuals when compared with those heavily infected [57].…”
Section: Discussionmentioning
confidence: 66%
“…12 These last authors suggested that this condition may be due to the continuous re-stimulation by evolving forms of the worm or that particularly in persons with an atopic genetic disposition and so, in this context, the higher levels of anti-Ascaris IgE would seem to reflect not only a marker of previous infection, but also a protective factor. 12,23 In fact, some studies have used the anti-Ascaris IgG isotype (not IgE) as a marker for chronic infections, 11,24 whereas some protective functions of the specific IgE molecule seem to contribute to the immunity of the host against different stages of the life cycle of the parasite (alterations in intestinal mobility and mucus production, associated to Th2 cytokines responses (IL-4, IL-13) and mast cell activation. 25,26 Furthermore, an analysis of the isotypic profile against antigenic molecules of A. lumbricoides demonstrates that in both non-infected patients and those with a low parasitic load, there were higher levels of specific IgE, thus suggesting a protective role for this immunoglobulin isotype.…”
Section: Discussionmentioning
confidence: 99%
“…IgE levels in a comparable group of children in West Germany were clearly lower (geometric mean 20.3 kU/l) [25]. In contrast, the geometric mean of total IgE in a study of schoolchildren in rural Ecuador was as high as 1,004 kU/l [26]. …”
Section: Discussionmentioning
confidence: 99%